INTERNALISASIPENDIDIKAN KARAKTER ISLAMI KEPADA ANAK SEKOLAH DASAR di SD Plus NURUL HIKMAH PAMEKASAN - Halimatus Sakdiyah (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
The Islamiceducation character of elementary school children is very important, as an effort to cultivate the students’ intelligence in thinking, acting and behaving in accordance with the noble values ​​that its’ become the identity, and can be realized in interaction with God, themselves, others and the environment as a manifestation. Schools are a strategic place for appear education character because the children of some circles will be educated at school. In addition, children spend most of their time at school, something they have been gotten in school will be affected the formation of their character. To realize a generation that has a strong character and strong faith and Islam, it is necessary to instill the values ​​of personality to the child. In this case, the role of educator is very important, especially when they were applying the teaching learning process to the students.To instill Islamic character education of elementary school, children need some methods that must be mastered by educators, such as exemplary, habituation, advice, attention (supervision), rewards and punishment. The educators can be given knowledge improvement, and can be internalized the spiritual values ​​to their students by using some methods.